A 12-year follow up of principles learned in a pediatric dentistry Master of Public Health dual degree program applied to professional practice - Ramos-Gomez, Francisco; Kinsler, Janni J.; Parkinson, Stephanie; Wang, Yan (Frontiers in Medicine, 2024)
Introduction Dental public health professionals play a critical role in preventing and controlling oral diseases. The purpose of this study was to assess the application of public health principles learned in a pediatric dentistry Master of Public Health (MPH) dual degree program to professional practice upon graduation. Methods Semi-structured interviews were conducted with pediatric dentistry/MPH dual degree alumni who graduated from the program between 2012 and 2023. Interview questions inquired about characteristics of patient population, location of providers’ clinic/organization, whether the program was worthwhile to their practice and application of principles learned in the program to their professional practice. Results Twenty of the 22 program alumni agreed to be interviewed. All alumni thought the program was extremely worthwhile to their practice. They felt the MPH component of the program gave them the public health background and tools they needed to provide comprehensive and holistic care to their patients. Additionally, all alumni reported applying the public health principles they learned in the program to their professional practice through leadership roles, research and teaching that focuses on oral disease prevention and the promotion of dental health. Discussion Given the importance of a dental public health professionals’ role in reducing oral health disparities at the population level, more pediatric dentistry MPH dual degree programs are urgently needed. Additionally, more research is necessary to demonstrate the effectiveness of these programs, which will be critical to helping ensure the value of a dual degree in dentistry and public health is recognized and promoted worldwide.